Peran Penyiar Dalam Program Podcast TV Show Di TV Muhammadiyah - Dafa Arkan Saputra; R. Hiru Muhammad (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
In broadcast programs, an announcer plays the role of controlling discussions that discuss various important topics in an interesting way so that the public gets the right information. The aim of this research is to determine the content of the podcast tv show program on tvMu and the role of the announcer in the podcast tv show program. tvMu created a program called Podcast tv Show, hosted by Fini Auliani. The podcast tv show program is an inspirational show for Muslims, especially Muhammadiyah members, but packaged in a more relaxed and creative way. The content broadcast is content that inspires the public from the sources presented. This research uses a qualitative method to explain the role of broadcasters of TV show podcast programs on tvMu. This research uses Boyd's theory that a broadcaster must have credibility, authority, clarity and clarity of voice volume, a strong personality, high professionalism, communicativeness and excellent appearance. The results of this research are that the TV show podcast program has experienced an increase in broadcast quality, such as innovation in developing broadcast themes. If previously it only discussed issues related to Muhammadiyah, now it has developed into discussing various economic, social, political and cultural issues. This has an impact on increasing the number of viewers or viewers on YouTube social media.